Analiza kodykologiczna manuskryptu Kraków, AiBKKK, Ms 45 .......... 75 - Ferfoglia, Susi; Baran, Wojciech (Graduał wawelski (Kraków, AiBKKK, Ms 45): Studium przypadku, 2025)
CODICOLOGICAL ANALYSIS OF THE MANUSCRIPT KRAKÓW, AIBKKK, MS 45The manuscript No. 45 from the collection of the Archive and Library of the Krakow Cathedral Chapter is the 15th-century gradual which was used for a few centuries during the religious service held in the Krakow cathedral. The current form of the codex was influenced by comprehensive conservation works carried out in 2017. Its dimensions are 46 × 33.5 cm. It consists of 302 parchment folios grouped into 32 quires. Elegant binding with brass buckles is an effect of the renovation. The wooden desk is the only piece of the original binding. The text of the antiphons was written by many scribes who used the so-called Gothic texture style in one column with 9 to 11 verses and the musical notation on 4 lines and on ff. 1r-15v on 5 lines. The codex contains rich decorations; the early simple initials in red, blue and black colours turn into more decorative multi-coloured shapes on later pages, sometimes even with gold inserts. Some of them are enriched by the motifs of human or animal faces. Miniatures in the form of initials depicting Biblical scenes and saints deserve special attention. In the whole manuscript few marginal and interlinear notes are found which can be dated from the 15th to the 19th century. They are usually identifications of liturgical feasts, invocations or additions to faded text or musical notes. The main part of the manuscript was written by one scribe between 1411 and 1420, however, the first four quires of the text were taken from various manuscripts. Some notes were added at a later stage.